1988
DOI: 10.1007/bf02406278
|View full text |Cite
|
Sign up to set email alerts
|

Enteral and parenteral feeding in the dysphagic patient

Abstract: Abstract. Thc inercasing rccognition of malnutrition among hospitalized patients has spawned a variety of sophisticated forms of nutritional support. Dysphagic patients, in particular, are easily identifiable and present with varying degrees of nutritional compromise thai complicate the underlying swallowing disorder. Choice of therapeutic modalities available and their relative risks and benefits are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…(subject opened lid on salad) ''Drink your milk'' (subject drank milk) ''Don't you want your gravy?'' (subject eats some gravy) Nonverbal (2) Points to salad (in conjunction with verbal cue) Points to gravy (in conjunction with verbal cue) 23 Partial assist (1) Wife hands subject dressing packet (subject proceeds to open) tially be manifested as slight prolongation or disorganization of bolus movement in the mouth resulting in an increased oral transit duration. This may be more prominent with consistencies that require more oral manipulation such as solids or greater oral control such as liquids.…”
Section: Swallowingmentioning
confidence: 99%
See 1 more Smart Citation
“…(subject opened lid on salad) ''Drink your milk'' (subject drank milk) ''Don't you want your gravy?'' (subject eats some gravy) Nonverbal (2) Points to salad (in conjunction with verbal cue) Points to gravy (in conjunction with verbal cue) 23 Partial assist (1) Wife hands subject dressing packet (subject proceeds to open) tially be manifested as slight prolongation or disorganization of bolus movement in the mouth resulting in an increased oral transit duration. This may be more prominent with consistencies that require more oral manipulation such as solids or greater oral control such as liquids.…”
Section: Swallowingmentioning
confidence: 99%
“…The inability to eat is the most life-threatening [2][3][4][5][6] of all the functional impairments in AD, with 50% of the patients losing the ability to feed themselves 8 years after diagnosis [7]. Altered eating behaviors in AD range from walking away from food at the table, to spitting out food, and choking on liquids and solids [8][9][10][11][12].…”
mentioning
confidence: 99%
“…This includes direct and informal healthcare costs and productivity losses due to mortality and morbidity. Stizmann and Mueller () found that 60% of deaths due to pneumonia are secondary to aspiration; while Doggett et al . () estimated that approximately 37% of dysphagic patients will develop pneumonia, and 3.8% of these will die if not included in a dysphagia programme.…”
Section: Introductionmentioning
confidence: 99%